Manajemen Hubungan Masyarakat Dalam Mengembangkan Lembaga Pendidikan (Studi Kasus di SMK Negeri 1 Dlanggu Mojokerto) - Muhammad Nur Hakim (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2019)
Abstract Schools and communities is a unity that can not be separated, as both mutual give and take. The school as a social institution and the institution of the community is given the responsibility of determining the fate of their nation to the next generation, while the society other than as consumers, also have roles and responsibilities the successful or not Organization of education. The community widely including learners, parents, Government, company/institution agency and so on. The main expectations of the performance of public relations is to attract people to care and trust as well as graduates or using the services offered by the institution. As is happening now, many agencies especially the institution suffered a crisis of confidence of the public in carrying out routine institution programs. See this, the role of public relations became very important in an internal institutional organisation or institution. Because of public relations practitioners are indeed function as an intermediary to bridge between the institutions represented by agencies that exist within the Community (or the community itself), as a result of public relations responsibility evenly against the institution It represents the associated with the community. Key words: public relations, educational institutions